Weighted differential evolution algorithm based pansharpening. Issue 22 (17th November 2021) - Günen, Mehmet Akif
ABSTRACT: Imaging Satellites acquire multispectral images, MI s, in low resolution, LR, and panchromatic images, PAN s, in high resolution, HR, due to some advantages provided in satellite design. The pansharpening, PS, is a super resolution image synthesis method that is used to generate the pansharpened image, PI, by fusion of PAN and MI . The use of PS process is unavoidable in applications such as efficient use of communication-bandwidth of imaging satellites and fusion of images derived from various image sensors. The PS process is a multi-step process consisting of various complex image processing stages, such as registration, resampling, synthesis, and fusion . The Weighted Differential Evolution Algorithm-based PS method, WDEPS, has been proposed in this paper. The WDEPS uses WDE to synthesize the intensity image, which is the blended-image of MI -bands. WDE has been used to compute the relevant image-blending weights, efficiently. In the experiments, several satellite images ( QuickBird-2, Ikonos-2, and GeoEye-1 ) with different spatial resolutions were used. The WDEPS's experimental results have been compared with 17 well-known PS methods by using 9 full-reference and 3 blind image quality assessment metrics. The experimental results exposed that WDEPS generates high-quality PI s than traditional PS methods used in the experimental aspect of qualitative and quantitative assessment.